Pemanfaatan Media Sosial sebagai Sarana Pemasaran Desa Wisata - Hendi Prasetyo; Novi Irawati; Zahrotun Satriawati (Ideas Publishing, 2023)
Tourism village marketing with social media is increasingly popular. The research aims to expand social media for tourism village marketing. The research method employed is qualitative, using the data collection technique of a library research. The results show that social media is effective as a marketing tool. Disadvantages include technology dependability, fierce competition, and the risk of poor use. Supporting factors are easy accessibility, broad market reach, low cost, sharing, and tagging features. The obstacles are limited access, infrastructure, unattractive content, limited skills, and competition. The right social media management strategy is expected to be able to increase visits, boost the local economy, and introduce the potential of tourism villages. Managers must ensure interesting, informative content and skill capacity to optimize social media in tourism village marketing.